Advances in Construction and Project Management Volume I: Construction and Project Management - Perera, Srinath; Chan, Albert P. C.; Amaratunga, Dilanthi; Hastak, Makarand; Lombardi, Patrizia; Senaratne, Sepani; Jin, Xiaohua; Sawhney, Anil (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The construction industry makes a significant contribution to the global economy. Effective management of construction projects is essential to ensuring timely completion that meets quality standards within a project's prescribed scope and budget. Furthermore, assuring sustainability is crucial to reducing the impact of construction on the environment. The construction industry is also affected by globalization and increasing susceptibility to disasters highlighting the need for health and safety and resilience in the industry, especially after global pandemics and natural disasters. Digitalization and industrialization pave the way to the solution or mitigation of numerous issues in the construction industry by transforming business operations, improving productivity and safety, ensuring quality and compliance to standards, increasing sustainability, among other measures. It is imperative for project managers and other construction stakeholders to be digitally oriented. This reprint comprises of a collection of cutting-edge research articles in construction and project management that explores advances in digital, sustainable, and industrialized construction solutions for prevalent issues in construction and project management and investigates the needs of health and safety and resilience in the construction industry.